Misdiagnosis of Extensive Maxillofacial Infection and Its Relationship with Periodontal Problems and Hyperglycemia - Statkievicz, Cristian [UNESP]; Faverani, Leonardo P. [UNESP]; Silva Gomes-Ferreira, Pedro Henrique [UNESP]; Ramalho-Ferreira, Gabriel [UNESP]; Garcia-Junior, Idelmo Rangel [UNESP] (Hindawi Ltd, 2016)
Background. Complex dental infections can reach distant areas of the alveolar process, invading the secondary fascial spaces. Objectives. This case report aims to show a misdiagnosis of odontogenic infection and a great need for dentist in the hospital environment. Case Report. A male patient presented facial asymmetry and trismus, while the facial CT examination showed a hyperdense mass involving the left masseteric, pterygomandibular, and superficial temporal regions. The patient was then referred to oral oncology center by emergency physician with cancer suspicion. After 15 days, the patient returned to the same emergency room and was attended by the surgical and maxillofacial trauma team, presenting tachycardia, tachypnea, dysphagia, and trismus. During anamnesis, the patient reported being an uncontrolled diabetic. In intraoral exam, a poor oral condition and generalized periodontitis were observed. Results. Correct diagnosis of odontogenic infection was established and adequately treated. Conclusions. Symptomatology bland may mask the severity of an infection; every increase in volume associated with trismus, poor oral hygiene with or without hyperglycemia should be heavily investigated for the presence of an infectious process. It emphasizes the importance of a dentist working with the physician in emergency room.